2005
DOI: 10.1136/adc.2004.062422
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalisations from birth to 5 years in a population cohort of Western Australian children with intellectual disability

Abstract: Aims: To describe the hospitalisation history in the first five years of life for all children born in Western Australia (WA) between 1983 and 1992 and diagnosed with intellectual disability (ID). Methods: Unit record linkage of the WA Midwives Collection, WA Intellectual Disability Database, and the WA Hospital Morbidity Dataset provided the population database of WA born children with and without ID. Affected children were divided into those co-affected with autism spectrum disorders (ASD), and those whose I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 9 publications
1
29
0
Order By: Relevance
“…Children with ID in this study had higher rates of dental admissions, as shown previously 8. Children with BD were also more likely to have a dental admission — this does not appear to have been previously reported.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Children with ID in this study had higher rates of dental admissions, as shown previously 8. Children with BD were also more likely to have a dental admission — this does not appear to have been previously reported.…”
Section: Discussionsupporting
confidence: 77%
“…The length of stay for same-day admissions was arbitrarily set at 0.5 days 8. Unless otherwise specified, a dental admission was defined as an admission to hospital where the principal diagnosis at discharge was coded using any of the following codes from the 9th Revision of the International Classification of Diseases, Clinical Modification (ICD-9): 520.0–529.9; V41.6; V52.3; V53.4; V58.5; or V72.2 (table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Australia, data linkage research concerning people with ID has largely occurred in WA, linking data from the WA Disability Services Commission or the IDEA database with various state-based registers such as birth defects, hospitalisations, and maternal health during pregnancy (e.g., Leonard, de Klerk, Bourke, & Bower, 2006;Petterson, Bourke, Leonard, Jacoby, & Bower, 2007;Williams et al, 2005). The IDEA database contains ongoing, population-based information on ID in WA based on medical and demographic data collected by the Disability Services Commission and supplemented with information provided by the Department of Education.…”
Section: Benefits Associated With Using Linked Datamentioning
confidence: 99%
“…A number of studies have found high rates of hospitalisation for injuries, infections, diseases and disorders of the nervous system and respiratory system, kidney and urinary tract problems, 'mental issues', dental conditions and skin disorders (Australian Bureau of Statistics., 2011; NSW Ministry of Health, 2012;Williams, Leonard, & Tursan D'Espaignet, 2005).…”
Section: Hospitalisationsmentioning
confidence: 99%